THICKNESS OPTIMIZATION OF ORGANIC SOLAR CELL BY OPTICAL AND 1D DRIFT-DIFFUSION ELECTRICAL MODELING - Hidayat, Anjar Taufik (Indonesian Physical Review, 2022)
Finding the best thickness combination of the active layer and the interlayer of organic solar cells is essential to optimizing and producing an efficient device. In this research, the thickness combination was graphed by two scan steps, i.e., the major scan (50 nm - interval) followed by the minor scan (10 nm - interval). The solar cell device was modeled by optical and 1D drift-diffusion modeling in the gvdm simulation software with P3HT: PCBM as the active layer and three different materials for the hole-selective layer (interlayer). The best power conversion efficiencies were 5.21, 4.14, and 5.22% when PEDOT: PSS, V2O5, and Spiro-OMeTAD were interlayer materials. The effective thickness for every interlayer material is 10 nm, while the effective thickness of the active layer is 220 nm (for PEDOT: PSS and Spiro-OMeTAD devices) and 230 nm (for V2O5 device). As a result, each device gives higher power conversion efficiency than that from the original setting of the software. Furthermore, this study's highest power conversion efficiency was higher than previously reported. These results suggest that scanning a more extensive range of layer thickness combinations is necessary to find the highest power conversion efficiency possible for every organic solar cell device